Renal cell carcinoma containing macroscopic fat on CT mimics an angiomyolipoma due to bone metaplasia without macroscopic calcification - Richmond, L (The British Institute of Radiology., 2010)
We report a case of renal cell carcinoma (RCC) containing foci of macroscopic fat, which were pathologically proven to be areas of osseous metaplasia. The macroscopic fat was not associated with calcification on the pre-operative CT scan. To our knowledge, there are no reported cases of RCC that contain osseous metaplasia without evidence of macroscopic calcification on CT. The finding is significant because standard imaging practice is to classify a renal mass containing intratumoral macroscopic fat that is not associated with calcification, ossification or invasion of perirenal or hilar fat as an angiomyolipoma.